Cancer adaptations: Atavism, de novo selection, or something in between?. (10th July 2017) - Thomas, Frédéric; Ujvari, Beata; Renaud, François; Vincent, Mark
Abstract : From an evolutionary perspective, both atavism and somatic evolution/convergent evolution theories can account for the consistent occurrence, and astounding attributes of cancers: being able to evolve from a single cell to a complex organized system, and malignant transformations showing significant similarities across organs, individuals, and species. Here, we first provide an overview of these two hypotheses, including the possibility of them not being mutually exclusive, but rather potentially representing the two extremes of a continuum in which the diversity of cancers can emerge. In reviewing the current literature, we also discuss the criteria that should be applied to discriminate between the two competing theories and to determine their relevant contributions to oncogenesis and cancer progression. Finally, we deliberate on the potential applications of this conceptual framework in developing novel treatment strategies. Abstract : Evolution theories, atavism initiating from the Precambrian and somatic/convergent evolution can both account for cancer adaptations. While they have distinct implications for therapies, the extent to which both contribute to tumorigenesis remains to be explored. Here we discuss this issue and suggest directions to discriminate between the two competing theories.